Uptake of adjuvant breast cancer treatments recommended by multi‐disciplinary meetings. Issue 7 (23rd January 2018) - Pattanasri, Melinda; Elder, Kenneth; Nickson, Carolyn; Cooke, Samuel; Machalek, Dorothy; Rose, Allison; Mou, Arlene; Collins, John P.; Park, Allan; De Boer, Richard; Phillips, Claire; Pridmore, Vicki; et al.
Abstract : Background: Adjuvant therapy for breast cancer is routinely discussed and recommended in multi‐disciplinary meetings (MDMs). Current literature explores how treatments received by patients differ from national guidelines; however, it does not explore whether treatment is concordant with MDMs. This study provides an Australian perspective on the uptake of MDM recommendations and reasons for non‐concordance. Methods: A retrospective cohort study of patients with breast cancer presented at The Royal Melbourne Hospital MDM in 2010 and 2014 to investigate the concordance between MDM recommendations and treatment received. Results: The study group comprised 441 patients (161 from 2010 and 280 from 2014). A total of 375 patients were included in the analyses. Overall, 82% of patients had perfect concordance between recommended and received treatment for all modes of adjuvant therapy. Concordance to endocrine therapy was higher for invasive cancers than ductal carcinoma in situ (97% versus 81%, P < 0.0001). Concordance to radiotherapy was high and did not differ according to type of cancer or surgery (ranging from 88 to 91%). Concordance to chemotherapy recommendations was high overall (92%) and did not vary with nodal status. Women aged over 65 years were least likely to be recommended for adjuvant therapy but most likely to concordant with the recommendation. Conclusions: Uptake of MDM‐recommended treatments is high. There is a minority of patients in whom MDM recommendations are not followed, highlighting that there are extra steps between recommendations at an MDM and decisions with patients. More attention to this issue is appropriate, and the reasons for non‐concordance warrant further study.